Narrando a diáspora: estudo sobre deslocamentos de africanos para o Brasil e políticas públicas para os migrantes - Eugênio, Luciana Daminelli (2018)
This dissertation is based on studies carried out by the research project about Culture, Identities and Migration, which is part of the research line Language and Culture, linked to the Post-Graduate Program in Language Sciences at Unisul. This research analyzes the narratives of migrants who chose Brazil as the destination country for their displacement and who, for some reason, suffered the impacts of Brazilian legislation for the resolution of legal conflicts. To do so, we assume that such narratives would reveal the limitations of Brazilian legislation and the living conditions of these migrants in Brazil, as well as their cultural identity. Therefore, it is made a review about the presence of migrants who constitute the African diaspora, because it refers to the perception of their culture, their profile, their social conditions, their apprehensions, their utopias, bringing to the surface the violations of human rights they suffered and, in most cases, the desire of living in Brazil, which overcomes the implications of resistance to the other. In Brazil, which has undergone a process of enslavement, colonization and mass immigration, and still strongly retains remnants of this past, in manifestations of prejudice and discrimination in relation to the African ethnicity, the recognition and the effectiveness of human rights of migrants still entail enormous challenges. The construction of the research was done through an exploratory study, based on the data collection, the qualitative methodology and the use of a specific research technique for narratives. The displacements of the Africans to Brazil are analyzed from the life testimonies of these subjects who are involved in such historical plots. Data collection was carried out based on the author's performance as a dative lawyer of 4th Region Federal Court . During the hearings of those assisted in the meeting to the demands of migrants which involves violations in labor law, the participants were asked about the authorization the register of data, with the preservation of their identities.